Inclusive Education Research Trends in Indonesia: A Bibliometric Analysis - Irawan, M. Ferry; Putri, Nadya Syafira (Educative: Jurnal Ilmiah Pendidikan, 2024)
Inclusive education is increasingly recognized as a critical component in ensuring equitable access to quality education for all students, regardless of their abilities or backgrounds. However, in Indonesia, the development and implementation of inclusive education practices remain uneven, with limited understanding of its growth and impact within the local context. This study aims to analyze inclusive education in Indonesia through bibliometric analysis, addressing six key questions: the most frequent keywords, trends in scholarly publications, prolific researchers, citation rates, influential journals, and collaboration patterns with other countries. Data from Scopus over the past decade resulted in 148 relevant articles, covering a wide range of topics from [Topic 1] to [Topic 2]. Findings reveal a predominant focus on inclusive education concepts in Indonesian literature, experiencing significant growth peaking in 2023. The study identifies 12 highly active authors with 98 articles and the top 10 most cited articles receiving 219 citations. Notably, research in 2020 achieved the highest citation rate, with 111 citations. The International Journal of Special Education emerged as the primary publication outlet. Indonesia collaborated with 13 countries, notably Malaysia, Australia, and the United States. These findings provide a robust foundation for developing inclusive education concepts and practices tailored to Indonesia's specific needs and context.